Pengembangan Buku Referensi Berbasis Riset Perbanyakan Tanaman Anggrek Dendrobium sp. Secara In Vitro - Nabilah Syahirah Azhari; Fauziyah Harahap; Ashar Hasairin (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2026)
This study aimed to develop a research-based reference book on the in vitro propagation of Dendrobium sp. orchids as a learning resource for the Plant Tissue Culture course. This study employed a Research and Development (R&D) method using the Four-D (4-D) development model, which consists of define, design, develop,  and  disseminate  stages.  The  reference  book  was  developed based on research findings on the shoot multiplication of Dendrobium sp. using combinations of the plant growth regulators Indole-3-Butyric Acid (IBA) and 6-Benzylaminopurine (BAP), as well as IBA and kinetin in Murashige and Skoog (MS) medium. Product feasibility was evaluated by two subject-matter experts, one instructional design expert, and one graphic design expert, while the practicality test involved one lecturer and 42 students from the Biology Education Study Program at the State Islamic University of North Sumatra. The results showed that the combinations of IBA with BAP and IBA with kinetin generally had no significant effect on shoot number, shoot length, leaf number, and shoot emergence time. The validation results showed that the developed reference book was categorized as feasible to highly feasible, with validation scores of 76.47% and 98.82% from the subject-matter experts, 87.50% from the instructional design expert, and 80.00% from the graphic design expert. Furthermore, the practicality evaluation obtained scores of 84.00% from the lecturer, 78.67% in the individual trial, 88.44% in the small-group trial, and 77.20% in the large-group trial, indicating that the book was practical to highly practical. Based on these findings, the research-based reference book was considered feasible and practical for use as a supplementary learning resource in the Plant Tissue Culture course. Keywords: 4-D Development Model, Dendrobium Sp., Research-Based Reference Book, Shoot Multiplication, Tissue Culture